Modern World Applications for Nano-Bio Materials: Tissue Engineering and COVID-19 - Melchor-Martínez, Elda M.; Torres Castillo, Nora E.; Macias-Garbett, Rodrigo; Lucero-Saucedo, Sofia Liliana; Parra-Saldívar, Roberto; Sosa-Hernández, Juan Eduardo (Frontiers in Bioengineering and Biotechnology, 2021)
Over the past years, biomaterials-based nano cues with multi-functional characteristics have been engineered with high interest. The ease in fine tunability with maintained compliance makes an array of nano-bio materials supreme candidates for the biomedical sector of the modern world. Moreover, the multi-functional dimensions of nano-bio elements also help to maintain or even improve the patients’ life quality most securely by lowering or diminishing the adverse effects of in practice therapeutic modalities. Therefore, engineering highly efficient, reliable, compatible, and recyclable biomaterials-based novel corrective cues with multipurpose applications is essential and a core demand to tackle many human health-related challenges, e.g., the current COVID-19 pandemic. Moreover, robust engineering design and properly exploited nano-bio materials deliver wide-ranging openings for experimentation in the field of interdisciplinary and multidisciplinary scientific research. In this context, herein, it is reviewed the applications and potential on tissue engineering and therapeutics of COVID-19 of several biomaterials. Following a brief introduction is a discussion of the drug delivery routes and mechanisms of biomaterials-based nano cues with suitable examples. The second half of the review focuses on the mainstream applications changing the dynamics of 21stcentury materials. In the end, current challenges and recommendations are given for a healthy and foreseeable future.